2009
DOI: 10.1517/13543780902845630
|View full text |Cite
|
Sign up to set email alerts
|

The role of telavancin in the treatment of MRSA infections in hospital

Abstract: Background: Serious infections caused by Gram-positive bacteria, particularly multi-drug resistant, are an important cause of morbidity and mortality in patients admitted to intensive care units. Thus, new antibiotics covering these pathogens are urgently needed. Objective: To review characteristics of telavancin, a novel antibiotic intended to use for treating infections caused by difficult Gram-positive bacteria, such as Staphylococcus aureus, resistant to meticillin or vancomycin, multi-drug-resistant Strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…MIC values (MIC 90 ) of tested strains between 0.25 and 1 mg/L have been reported in an over 4,500 isolates of methicillin-susceptible S. aureus (MSSA) and MRSA worldwide 11–17. In several studies, telavancin MICs for MRSA ranged from two to eight times lower than those observed for vancomycin, teicoplanin, and linezolid [ 83 ]. Similarly, coagulase-negative staphylococci (CoNS) exhibited MIC 90 values between 0.25 and 1 mg/L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIC values (MIC 90 ) of tested strains between 0.25 and 1 mg/L have been reported in an over 4,500 isolates of methicillin-susceptible S. aureus (MSSA) and MRSA worldwide 11–17. In several studies, telavancin MICs for MRSA ranged from two to eight times lower than those observed for vancomycin, teicoplanin, and linezolid [ 83 ]. Similarly, coagulase-negative staphylococci (CoNS) exhibited MIC 90 values between 0.25 and 1 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, coagulase-negative staphylococci (CoNS) exhibited MIC 90 values between 0.25 and 1 mg/L. Telavancin also proved to have an excellent activity against MRSA and CoNS with reduced susceptibility to glycopeptides, together with both vancomycin-susceptible and resistant enterococci [ 83 ]. The potent anti-staphylococcal activity of telavancin may lead to consider this lipoglycopeptide as an alternative to vancomycin in cases of difficult-to-treat MRSA infections [ 84 , 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…Telavancin distributed into lung tissue with epithelial lining fluid concentrations of approximately two-to eightfold above the MIC 90 of S. aureus for 24 h. Post antibiotic effect of 4e6 h were [28].…”
Section: Telavancinmentioning
confidence: 97%
“…Large randomized Phase 2 and 3 clinical trials on the efficacy and safety of telavancin in treating complicated skin and skin structure infections reported that telavancin was non-inferior to standard treatment, mostly vancomycin [42].…”
Section: Telavancinmentioning
confidence: 99%